Interaction of nitrate and folate on the risk of breast cancer among postmenopausal women - Inoue-Choi, Maki (2012)
Ingested nitrate can be endogenously reduced to nitrite, which may form N-nitroso compounds, known potent carcinogens. However, some studies have reported no or inverse associations between dietary nitrate intake and cancer risk. These associations may be confounded by a protective effect of folate, which plays a vital role in DNA repair. We evaluated the interaction of dietary and water nitrate intake with total folate intake on breast cancer risk in the Iowa Women’s Health Study. Dietary intake was assessed at study baseline. Nitrate intake from public water was assessed using a historical database on Iowa municipal water supplies. After baseline exclusions, 34,388 postmenopausal women and 2,875 incident breast cancers were included. Overall, neither dietary nor water nitrate was associated with breast cancer risk. Among those with folate intake ≥400 μg/d, breast cancer risk was significantly increased in public water users with the highest nitrate quintile (HR=1.40, 95%CI=1.05–1.87) and private well users (HR=1.38, 95%CI=1.05–1.82) compared to public water users with the lowest nitrate quintile; in contrast, there was no association among those with lower folate intake. Our findings do not support a previous report of increased risk of breast cancer among individuals with high dietary nitrate but low folate intake.